Strategi Perencanaan Tata Ruang Berbasis Mitigasi Bencana Kebakaran Di Kota Makassar - Nini Apriani Rumata; Firdaus yusuf (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
Makassar City has a very rapid development from year to year. However, this development is not matched by the provision of infrastructure that can cope with fire disasters that have the potential to occur. In addition, the completeness of regulations and guidelines that can serve as a corridor in planning for the prevention and handling of fire disasters is not yet fully available. This study aims to determine the level of vulnerability of Makassar City to fire disasters so that strategies can be formulated in spatial planning based on fire disaster mitigation. The analysis used in this study is descriptive analysis to describe current conditions, Super Impose (Overlay) analysis using GIS applications to map Makassar City according to indicators that affect the level of vulnerability of the area to fire disasters. After that, network analysis is carried out to be able to map the movement network so that it can ensure the time and distance of firefighters to reach the fire location.